Ranibizumab for Macular Edema Secondary to Central and Branch Retinal Vein Occlusion in Patients Younger Than 50 Years of Age. (18th June 2020) - Battaglia Parodi, Maurizio; Romano, Francesco; Arrigo, Alessandro; Mercuri, Stefano; Franceschi, Alessandro; Bandello, Francesco
Abstract : Background . To determine the effectiveness of intravitreal ranibizumab (IVR) approach over 1-year follow-up in patients younger than 50 years old with central and branch retinal vein occlusion (RVO) complicated by macular edema (ME). Methods . Prospective, open-label case series. Patients initiating IVR injections from January 2015 to May 2017 were consecutively recruited. Each patient underwent monthly ophthalmic examination and structural OCT over 12 months. A single IVR injection was administered at baseline, followed by a PRN regimen. Outcome measures are best-corrected visual acuity (BCVA); central foveal thickness (CFT); number of IVR injections; subretinal fluid (SRF); epiretinal membrane; and outer retinal layer (ORL) status. Results . Thirty-eight patients (27 males) were included in the study. At follow-up, mean BCVA improved from 0.40 ± 0.17 to 0.10 ± 0.10 LogMAR in patients with central RVO and from 0.39 ± 0.19 to 0.19 ± 0.07 LogMAR in those with branch RVO, with 20 eyes gaining ≥3 ETDRS lines. In addition, mean CFT significantly decreased in both subgroups at the end of follow-up. All patients with SRF at baseline (9) disclosed complete resolution after 1 year. Likewise, ORL appeared reconstituted in most cases. At 12 months, 3.6 ± 2.4 and 4.4 ± 2.4 IVR injections were required for central and branch RVO, respectively, with only 5 eyes showing ME persistence. Conclusions . Our study indicates that IVR injections can be a valid therapeutic option in patients under 50 years of age with ME secondary to RVO.